2019
DOI: 10.3390/healthcare7020073
|View full text |Cite
|
Sign up to set email alerts
|

Perspectives of Stakeholders on Technology Use in the Care of Community-Living Older Adults with Dementia: A Systematic Literature Review

Abstract: Although technology has the potential to promote aging in place, the use of technology remains scarce among community-living older adults with dementia. A reason might be that many stakeholders are involved who all have a different perspective on technology use (i.e., needs, wishes, attitudes, possibilities, and difficulties). We systematically searched the literature in order to provide an overview of perspectives of different stakeholders on technology use among community-living older adults with dementia. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

7
41
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(51 citation statements)
references
References 74 publications
7
41
0
Order By: Relevance
“…The findings in this review are also commensurate with four others from the last year, and the AT reviewed are similar [66][67][68][69][70]. AT interventions can be beneficial to quality of life, social interaction, reducing neuropsychiatric symptoms such as depression, anxiety, and agitation, but continued use of AT becomes problematic due to the progressive nature of dementia [69,70].…”
Section: Summary Of Evidencesupporting
confidence: 78%
See 1 more Smart Citation
“…The findings in this review are also commensurate with four others from the last year, and the AT reviewed are similar [66][67][68][69][70]. AT interventions can be beneficial to quality of life, social interaction, reducing neuropsychiatric symptoms such as depression, anxiety, and agitation, but continued use of AT becomes problematic due to the progressive nature of dementia [69,70].…”
Section: Summary Of Evidencesupporting
confidence: 78%
“…AT interventions can be beneficial to quality of life, social interaction, reducing neuropsychiatric symptoms such as depression, anxiety, and agitation, but continued use of AT becomes problematic due to the progressive nature of dementia [69,70]. Both carers and PWD shared observations on aspects of AT such as ease of use, stability and flexibility of technology, and the importance of privacy and confidentiality [67,68]. One finding that was not in this review was an improvement in pain management, as was found in a review from 2019 [69].…”
Section: Summary Of Evidencementioning
confidence: 99%
“…This special issue of Healthcare on "Creating Age-Friendly Communities: Housing and Technology" is timely, comprising twelve papers [16][17][18][19][20][21][22][23][24][25][26][27] that traverse and intersect across the fields of gerontology, health and social care, social sciences and gerontechnology.…”
mentioning
confidence: 99%
“…Thus, the accepted papers surrounding dementia have focused on the perspectives of healthcare professionals in conjunction with meaningful activities for individuals diagnosed with dementia residing in a nursing home environment [16,25], and installing and using aids and adaptations within the home to create a physical environment that is more dementia-friendly [19]. Furthermore, exploring and understanding technology use associated with care of individuals living with dementia in the community from the perspective of stakeholders [23] is equally important as a systematic review to ascertain the current landscape and offer readers the ability to see what areas need greater improvement and expansion.…”
mentioning
confidence: 99%
See 1 more Smart Citation